The Importance of Directional Policy Matrix for Sri Lankan Marketers- A Theoretical Perspective - Selvarajan, P. (Rajarata University of Sri Lanka, 2011)
The study investigates the importance of Directional Policy Matrix (DPM) for Sri Lankan marketers. Understanding of theories in marketing has a great impact of marketing practices, since the survival and sustainability of organizations are based on their market strength and market attractiveness. As such the BCG matrix was evolved into the DPM. In the DPM developed by Mc Donald and Payne (1996) market share and market growth rate were replaced by business strength and market attractiveness respectively. Market attractiveness includes the size of the market, expected growth, lack of competition, profit margins within the market and other favorable political and socio- economic conditions. On the other hand business strength is determined by the sales volume, the product’s reputation, reliability of service and competitive pricing. The main objective of the study is to understand the relevance of the DPM for Sri Lankan marketers. There are various theories and literatures reviewed to get the right understanding. The findings showed that the quadrant ‘grow’ indicated that the company can grow during the high market attractive and low business strengths. Then it moves to high – high position called as ‘invest’. In this position the sales will improve. The third quadrant ‘harvest’ showed a decline in sales which leads to a low market attractive position. The final quadrant ‘divest’ was the low – low position and the company is likely to reduce or even withdraw and choosing to spend resources on new or existing product which offer the prospect of greater returns. The author also found that the Product Life Cycle plays a major role in determining the positions of companies in the DPM and take decisions on product planning, forecasting and promotional activities.
Keywords: Directional Policy Matrix; Market Attractiveness; Business Strength; Product Life Cycle; Sri Lankan Marketers